Back Cover: Indolizino[5, 6‐b]quinoxaline Derivatives: Intramolecular Charge Transfer Characters and NIR Fluorescence (Chem. Asian J. 11/2015). Issue 11 (8th October 2015) - Kojima, Mitsuru; Hayashi, Hironobu; Aotake, Tatsuya; Ikeda, Shinya; Suzuki, Mitsuharu; Aratani, Naoki; Kuzuhara, Daiki; Yamada, Hiroko
<x xml:space="preserve">Abstract</x> Indolizino[5, 6‐b]quinoxaline derivatives with a push–pull structure are reported. They showed an intramolecular charge‐transfer character and were strongly fluorescent in aprotic solvents. The π‐expanded α–α linked dimer of indolizino[5, 6‐b]quinoxaline was serendipitously obtained to show NIR absorption above 800 nm and the fluorescence edge reached to 1400 nm. More information can be found in the Communication on page 2437 by Hiroko Yamada et al. (DOI:10.1002/asia.201500597).